PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KEDELAI ( Glycine max L.Merrill ) PADA BERBAGAI TINGKAT PENAUNGAN TAHAP KEDUA - Muhammad Iqbal; Lisa Mawarni; Charloq Charloq (Jurnal Agroekoteknologi, 2013)
This research aims to know the growth and production various types of soy beans in the second stage various levels of shade. This research was done on Faculty of Agriculture field Universitas Sumatera Utara. On July until October 2011 in Medan. This research was used split plot design  factorial  methods with two factors, shade (0%, 20%, 40%, 60%) as the main plot and varieties (Anjasmoro, Pangrango, Tanggamus, Nanti) as subplot. The result showed that the shades to significant effect against plant height, the number of branches on the main stem, number of beans per plant, number of seeds per plant, production per plot, weight of 100 seeds. Varieties  factor gave significant  effect to percentage of germination, number of seeds per plant, weight of 100 seeds. interaction shading and varieties was significant effect to percentage of germination. ________________________________________________________________________________ Key words: shade, varieties,and  soybean